Preizkus integralnega monitoringa populacij velikih zveri in njihovih ključnih plenskih vrst na območju gojitvenega lovišča Jelen-Snežnik v obdobju 1991-2003 - Adamič, Miha (Gozdarski vestnik, 2006)
In 1991, we launched the monitoring of the presence of large carnivores and their main prey species in the wildlife reserve of Jelen-Snežnik (in the form of a comprehensive survey). To enable spatial mapping of observed animals, thearea of the wildlife reserve was divided into 306 numbered permanent quadrants sized 1 x 1 km. The findings of continuous monitoring in the period 1991-2003 show that the monitoring method for wildlife populations, when applied in large areas, enables us to make conclusions on population changes, on relationships between various populations of wildlife and conclusions on relationships between populations and habitat changes.
Keywords: zveri; plenilci; lovišča